Influence of corneal guttae and nuclear cataract on contrast sensitivity - Augustin, Victor A.; Weller, Julia M.; Kruse, Friedrich; Tourtas, Theofilos (British Journal of Ophthalmology, 2020)
AIMS: To evaluate the contrast sensitivity in patients with nuclear cataract and corneal guttae compared to patients with nuclear cataract without guttae. METHODS: In this retrospective, single-centre case series, 50 eyes of 50 patients fulfilling the inclusion criteria were enrolled. Patients with corneal guttae and nuclear cataract (n=25, study group) underwent triple Descemet membrane endothelial keratoplasty (DMEK). Patients with nuclear cataract and healthy corneas underwent cataract surgery (n=25, control group). Inclusion criteria were preoperative best-corrected visual acuity ≥20/40, no corneal oedema and similar lens opacity (nuclear opalescence 2.0-2.9). Outcome measures included MARS letter and OPTEC 6500P contrast sensitivity test, corneal volume, central corneal thickness and anterior and posterior corneal densitometry. RESULTS: Preoperative MARS letter and OPTEC 6500P contrast sensitivity was significantly worse in the study group (MARS: p<0.001; OPTEC 6500P: p<0.007 at low spatial frequencies in daylight with and without glare and nightlight without glare). After surgery, there was no significant difference in MARS letter contrast sensitivity between groups (p=0.225). OPTEC 6500P contrast sensitivity remained significantly lower in the study group in daylight and nightlight with and without glare at most spatial frequencies (p<0.01) postoperatively. Preoperative and postoperative corneal volume, central corneal thickness and anterior corneal densitometry were equal in both groups (p>0.05). Posterior densitometry was significantly higher in the study group than in the control group preoperatively (p<0.001) but turned into equal values postoperatively (p=0.07). CONCLUSIONS: Corneal guttae cause an additional significant decrease in contrast sensitivity in eyes with nuclear cataract. This is in favour of performing a triple DMEK even in eyes with a visual acuity of ≥20/40.
CRIS-Team Scopus Importer:2020-10-09